Effect of Gypsum Waste Stabilization in Clay Soil on California Bearing Ratio Value - Muthia Anggraini; Yustinus Sitorus; Widya Apriani (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2024)
The problem that occurs in road construction is the low CBR value of the subgrade. Advances in stabilization technology for soil improvement by mixing clay with a mixture of gypsum powder which has elements of the compound Calcium Oxide (Cao), Potassium (Ca), Water (H₂O), Hydrogen (H), and Sulfur (S), so it is necessary to conduct further research and testing in the laboratory with the aim of obtaining the California bearing ratio value on variations in gypsum powder mixing. The research method used is an experimental method in the laboratory with reference to the 2018 Bina Marga General Specifications. With mixing variations of 5%, 10%, 15% and 20% gypsum waste. The soil used in this research was taken from Jalan Badak area, Sail, Tenayan Raya sub-district, Pekanbaru City, Riau which was then tested in the laboratory by testing the specific gravity, soil density and california bearing ratio. The results of laboratory testing, it can be concluded that the addition of 5%, 10%, 15% and 20% gypsum has increased the CBR value, namely with a CBR value of 1.70% to 12.50%. The CBR value has met the Binamarga specification, 2018 which is 6%. So from the results of the equation obtained, it shows a positive relationship, namely the optimum moisture content (OMC) value increases with the increase in the California Bearing Ratio (CBR) value.